If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 5n = 6m + -2n Solving 3m + 5n = 6m + -2n Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 3m + -6m + 5n = 6m + -6m + -2n Combine like terms: 3m + -6m = -3m -3m + 5n = 6m + -6m + -2n Combine like terms: 6m + -6m = 0 -3m + 5n = 0 + -2n -3m + 5n = -2n Add '-5n' to each side of the equation. -3m + 5n + -5n = -2n + -5n Combine like terms: 5n + -5n = 0 -3m + 0 = -2n + -5n -3m = -2n + -5n Combine like terms: -2n + -5n = -7n -3m = -7n Divide each side by '-3'. m = 2.333333333n Simplifying m = 2.333333333n
| 5(2)+15x=10 | | 21x^2-6x+13=0 | | x^2+9y^2=28 | | 3x+2-x-5=7x+6-4x-2 | | -6(2t+10)=-24 | | 3(4x+1)=5x-8x | | .5b^2=16 | | 5(3s+7)=185 | | 2(f-8)=-2 | | 9x-94=116-5x | | 5w+16=66 | | .5b^2-81=0 | | 1.3x=-13 | | -3x+17+5x-7=-5x+2+7x-10 | | 3x+10=33+2x | | 0.5-3-x=6.5 | | -5+5u=-10 | | Y^2-4y-x=0 | | 3(2l+7)=63 | | 5-(a-4)=-2x+1 | | 8a-a=7a-6 | | 10(s-4)=-83 | | 2x+8+7+8x=4x+20+x+5 | | x^2+3x=304 | | 2(7x+2)+6=14x-10 | | -4[4-(3b+4)]=5-4(3b+8) | | 3(t-1)=9t | | -(c-20)=-2 | | x=6y-2x-9 | | x^4+3x^3+9x^2+27x=0 | | 7x+3-4x+15=6x+20-3x-2 | | x=gy-2x-9 |